Handbook of digital games and entertainment technologies - Nakatsu, Ryohei; Rauterberg, Matthias; Ciancarini, Paolo, 1959- (Springer, 2016)
The topics treated in this handbook cover all areas of games and entertainment technologies, such as digital entertainment; technology, design/art, and sociology. The handbook consists of contributions from top class scholars and researchers from the interdisciplinary topic areas. The aim of this handbook is to serving as a key reference work in the field and provides readers with a holistic picture of this interdisciplinary field covering technical issues, aesthetic/design issues, and sociological issues. At present, there is no reference work in the field that provides such a broad and complete picture of the field. Engineers and researchers who want to learn about this emerging area will be able to find adequate answers regarding technology issues on digital entertainment. Designers and artists can learn how their skills and expertise can contribute to this emerging area. Also researchers working in the field of sociology and psychology will find how their experience and knowledge are connected to other areas such as technology and art/design. Although topics are written by foremost experts from the field, the description for each topic has been intended to be easily understandable but yet comprehensive enough so that it caters not only for the experts but also beginners and students in the field.